স্বাধীনতা সংগ্রামে ভারতের জাতীয় কংগ্রেস, ১৮৮৫-১৯৪৭ - ত্রিপাঠী, অমলেশ, ১৯২১-
This volume presents an analytical history of India's struggle for freedom and the role played in it by the Indian National Congress. Drawing on statistical analysis and exhaustive research, it provides a comprehensive account of the Independence movement, encompassing events such as the extremist-moderate split in the Congress, Morley-Minto reforms, Round Table Conferences, the Quit India Movement, and the Partition.